PENERAPAN METODE JARIMATIKA UNTUK MENINGKATKAN KEMAMPUAN OPERASI HITUNG PERKALIAN BAGI SISWA TUNARUNGU - Ridha Purnama Sari; Mustafa Mustafa; Syamsuddin Syamsuddin (-, 2024)
The problem in this research is that deaf students in class VIII at SLB B YPPLB Makassar have not been able to calculate multiplications from 6 to 9 correctly. The formulation of this research problem is 1). What is the ability of multiplication calculation operations for Deaf students at SLB B YPPLB Makassar? 2). How is the application of Jarimatika to improve the ability of multiplication calculation operations for Deaf students at SLB B YPPLB Makassar? 2). How can the ability to calculate multiplication operations improve for Deaf students at SLB B YPPLB Makassar? The aim of this research is to determine: 1) The ability of multiplication calculation operations for Deaf students at SLB B YPPLB Makassar. 2) Application of Jarimatics to improve the ability of multiplication calculation operations for Deaf students at SLB B YPPLB Makassar. 3) Increasing the ability to calculate multiplication operations for Deaf students at SLB B YPPLB Makassar. The approach in this research is a quantitative approach with descriptive research type. The subjects involved in the research were Deaf students in class VIII at SLB B YPPLB Makassar with the initials BD. The data collection technique was carried out using a written test. Data analysis was carried out by comparing the ability to calculate multiplication operations before and after applying the Jarimati Ka method to students with intellectual disabilities. It was concluded that the results of research on the ability of multiplication calculation operations in Deaf students in class VIII at SLB B YPPLB Makassar through the application of the Jarimatika method showed an increase, namely before the application of the Jarimatika method students were only able to answer 2 questions correctly and after the application of the Jarimatika method students were able to answer 8 questions correctly.